Impact of the morphological signs of Stage II corpus uteri cancer on the occurrence of recurrences and metastases - E. A. Mustafina; V. V. Barinov; M. A. Shabanov; V. I. Peskova; L. I. Bokina (ABV-press, 2014)
The paper gives the rates of recurrences and metastases occurring after primary therapy in 109 patients with Stage II corpus uteri cancer (CUC) treated at the Unit of Gynecology, N.N. Blokhin Russian Cancer Research Center.The distribution of patients with Stages IIA and IIB CUC is shown by the rates of recurrences and metastases; the time of their emergence is defined; the mean survival is estimated in patients with progressive CUC. The distribution of patients with recurrent Stage II CUC and separately its metastases is considered in relation to the early unstudied morphological characteristics of primary tumor.